Factors associated with refractory pain in emergency patients admitted to emergency general surgery - Gilliam, William (World J Emerg Med, 2021)
BACKGROUND: Oligoanalgesia in emergency departments (EDs) is multifactorial. A previous study reported that emergency providers did not adequately manage patients with severe pain despite objective findings for surgical pathologies. Our study aims to investigate clinical and laboratory factors, in addition to providers’ interventions, that might have been associated with oligoanalgesia in a group of ED patients with moderate and severe pains due to surgical pathologies. METHODS: We conducted a retrospective study of adult patients who were transferred directly from referring EDs to the emergency general surgery (EGS) service at a quaternary academic center between January 2014 and December 2016. Patients who were intubated, did not have adequate records, or had mild pain were excluded. The primary outcome was refractory pain, which was defined as pain reduction <2 units on the 0–10 pain scale between triage and ED departure. RESULTS: We analyzed 200 patients, and 58 (29%) had refractory pain. Patients with refractory pain had significantly higher disease severity, serum lactate (3.4±2.0 mg/dL vs. 1.4±0.9 mg/dL, P=0.001), and less frequent pain medication administration (median [interquartile range], 3 [3–5] vs. 4 [3–7], P=0.001), when compared to patients with no refractory pain. Multivariable logistic regression showed that the number of pain medication administration (odds ratio [OR] 0.80, 95% confidence interval [95% CI] 0.68–0.98) and ED serum lactate levels (OR 3.80, 95% CI 2.10–6.80) were significantly associated with the likelihood of refractory pain. CONCLUSIONS: In ED patients transferring to EGS service, elevated serum lactate levels were associated with a higher likelihood of refractory pain. Future studies investigating pain management in patients with elevated serum lactate are needed.